Methods and Procedural Forms of Protection of Personal Non-Property Patent Rights in Russia - Borisovich Sitdikov, Ruslan; Mansurovich Sadykov, Ravil; Gennadievich Valery, Golubtsov (Cuestiones Políticas, 2020)
The article discusses the legal regulation of the application of civil law methods of non-patrimonial personal rights in the protection of patent rights. Methodologically, the scientific method and the technique of documentary research close to legal hermeneutics were made. By way of conclusion, everything indicates that there is no mandatory administrative procedure for resolving authorship disputes in the patent dispute chamber in Russia. In addition, it was revealed that the provisions of Part 4 of the Civil Code of the Russian Federation with respect to the Protection of Non-Property Personal Patent and Intellectual Rights were unsuccessfully established and created legal uncertainty, as only part of the above methods of civil and personal rights have worked in non-property litigation. As a recomjunction, it is proposed to extend the scope of Article 1407 of the Civil Code of the Russian Federation "publication of the judicial decision on patent infringement" and related administrative procedures for cases of violation of non-patrimonial personal patent rights.